The Effect of Video Learning Media on the Ability to Make Class IV Collage Works at SD Negeri 124 Mampotu, Amali District, Bone Regency - Novia Jusmita (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research is a quantitative research design research one group pretest-posttest design which aims to determine whether or not there is a significant influence of video learning media on the ability to make collage works of fourth grade students of SD Negeri 124 Mampotu. The variables in this study were video learning media (independent variable), and the ability to make collages (dependent variable). The population of this research is all the fourth grade students of SD Negeri 124 Mampotu totaling 31 people. The sample used in this study is a saturated sample, namely class IV SD Negeri 124 Mampotu. The research data were obtained by giving tests in the form of multiple choice questions and essays. Data collection techniques used are tests and observations. The data analysis technique is inferential analysis using paired sample t-test. The results obtained in this study are that there is a significant effect of video learning media on students' ability to make collages.